Cross-Border Supply Chain Finance Platform: Synergizing International Trade and Financial Strategy for Resilient Supply Chains in Southeast Asia - Hidayah, Nazilatul; Dumasari Siregar, Dr. Diyah; Priyanto, Riko; Nugroho, Imam Aldi (Journal Research of Social Science, Economics, and Management, 2026)
This study examines the development of a Cross-Border Supply Chain Finance Platform (CB-SCFP) that synergizes international trade mechanisms and financial strategies to strengthen regional resilience. The objective is to address persistent challenges of payment delays, liquidity shortages, and fragmented trade-finance linkages in ASEAN economies. Current debates on supply chain resilience tend to treat trade policy and financial strategy as separate domains, resulting in fragmented solutions. This paper addresses the research question: How can the integration of international trade and financial strategies through a digital finance platform enhance the resilience of Southeast Asia’s supply chains? The novelty of this study lies in introducing an integrated CB-SCFP model that combines trade facilitation, digital financing tools, and risk mitigation instruments across multiple ASEAN markets. Unlike prior studies focusing narrowly on trade agreements or financial hedging mechanisms, this research develops a unified conceptual and empirical framework linking trade flows with supply chain finance innovation. Methodologically, the study employs a qualitative-descriptive approach with triangulation. Data were gathered through 25 semi-structured interviews with exporters, importers, and financial practitioners in Indonesia, Malaysia, and Singapore, supported by policy analysis and secondary data from trade reports (2019-2024). A conceptual modeling technique was used to illustrate the structural components and operational functions of the CB-SCFP. The findings indicate that the CB-SCFP reduces average payment delays by 18%, enhances liquidity access for SMEs by 24%, and mitigates currency risk through automated hedging modules.